Quality of fresh-cut purple cabbage stored at modified atmosphere packaging and cold-chain transportation. Issue 1 (1st January 2020) - Li, He; Li, Xuanlin; Wang, Ranran; Xing, Yage; Xu, Qinglian; Shui, Yuru; Guo, Xunlian; Li, Wenxiu; Yang, Hua; Bi, Xiufang; Che, Zhenming
ABSTRACT: The effects of modified atmosphere packaging (MAP) and transportation conditions on the quality of fresh-cut (FC) purple cabbage during cold-chain transportation at 4°C for 20 days were investigated. The weight loss and respiratory intensity of FC purple cabbage were found to be significantly prevented and inhibited, measuring from 0% and 5.92 mg CO2 kg −1  h −1 to 3.47% and 5.05 mg CO2 kg −1  h −1, respectively, at the end of storage, through the use of argon-MAP and shock-absorbing packing material during transportation. Furthermore, the contents of vitamin C (VC) and total soluble solids (TSS) also decreased in the FC cabbage, to 21.6 mg 100g −1 FW and 13.88%, respectively. Additionally, the polyphenol oxidase (PPO) activity and total phenol (TP) content of the treated purple cabbage were inhibited effectively. After storage for 20 days, the sensory comprehensive score, L*, a*, and b* values of the processing group 10 were 8.5, 6.82, 5.55 and 1.54, respectively. These results demonstrate that the combined treatment of argon-MAP and shock-absorbing transportation can be considered efficient in preserving the quality of FC purple cabbage during storage.